(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
The article presents the results of a theoretical study on determining the tension force of the pressure spring applied to the bobbin in loosening the knot between the rows of cotton. In this case, it was determined using analytical expressions that the tension force of the pressure spring of the parallelogram mechanism with the roller should be in the range of 353-358 N in order for it to sink to the specified depth.